Dioxolanone-anchored poly(allyl ether)-based cross-linked dual-salt polymer electrolytes for high-voltage lithium metal batteries - Vijayakumar, Vidyanand; Diddens, Diddo; Heuer, Andreas; Kurungot, Sreekumar; Winter, Martin; Nair, Jijeesh Ravi (ACS Applied Materials & Interfaces, 2020)
Novel cross-linked polymer electrolytes (XPEs) are synthesized by free-radical copolymerization induced by ultraviolet (UV)-light irradiation of a reactive solution, which is composed of a difunctional poly(ethylene glycol) diallyl ether oligomer (PEGDAE), a monofunctional reactive diluent 4-vinyl-1,3-dioxolan-2-one (VEC), and a stock solution containing lithium salt (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) in a carbonate-free nonvolatile plasticizer, poly(ethylene glycol) dimethyl ether (PEGDME). The resulting polymer matrix can be represented as a linear polyethylene chain functionalized with cyclic carbonate (dioxolanone) moieties and cross-linked by ethylene oxide units. A series of XPEs are prepared by varying the [O]/[Li] ratio (24 to 3) of the stock solution and thoroughly characterized using physicochemical (thermogravimetric analysis-mass spectrometry, differential scanning calorimetry, NMR, etc.) and electrochemical techniques. In addition, quantum chemical calculations are performed to elucidate the correlation between the electrochemical oxidation potential and the lithium ion-ethylene oxide coordination in the stock solution. Later, lithium bis(fluorosulfonyl)imide (LiFSI) salt is incorporated into the electrolyte system to produce a dual-salt XPE that exhibits improved electrochemical performance, a stable interface against lithium metal, and enhanced physical and chemical characteristics to be employed against high-voltage cathodes. The XPE membranes demonstrated excellent resistance against lithium dendrite growth even after reversibly plating and stripping lithium ions for more than 1000 h with a total capacity of 0.5 mAh cm(-2). Finally, the XPE films are assembled in a lab-scale lithium metal battery configuration by using carbon-coated LiFePO4 (LFP) or LiNi0.8Co0.15Al0.05O2 (NCA) as a cathode and galvanostatically cycled at 20, 40, and 60 degrees C. Remarkably, at 20 degrees C, the NCA-based lithium metal cells displayed excellent cycling stability and good capacity retention (>50%) even after 1000 cycles.
Keywords: cross-linked polymer electrolyte; dual-salt electrolyte; high-voltage cathode; lithium metal battery; solvent-free photopolymerization

In situ cross-linked nonaqueous polymer electrolyte for zinc-metal polymer batteries and hybrid supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Kurian, Maria; Torris, Arun; Dilwale, Swati; Badiger, V. Manohar; Winter, Martin; Nair, Jijeesh Ravi; Kurungot, Sreekumar (Small, 2020)
This work reports the facile synthesis of nonaqueous zinc-ion conducting polymer electrolyte (ZIP) membranes using an ultraviolet (UV)-light-induced photopolymerization technique, with room temperature (RT) ionic conductivity values in the order of 10(-3)S cm(-1). The ZIP membranes demonstrate excellent physicochemical and electrochemical properties, including an electrochemical stability window of >2.4 V versus Zn|Zn(2+)and dendrite-free plating/stripping processes in symmetric Zn||Zn cells. Besides, a UV-polymerization-assisted in situ process is developed to produce ZIP (abbreviated i-ZIP), which is adopted for the first time to fabricate a nonaqueous zinc-metal polymer battery (ZMPB; VOPO4|i-ZIP|Zn) and zinc-metal hybrid polymer supercapacitor (ZMPS; activated carbon|i-ZIP|Zn) cells. The VOPO(4)cathode employed in ZMPB possesses a layered morphology, exhibiting a high average operating voltage of approximate to 1.2 V. As compared to the conventional polymer cell assembling approach using the ex situ process, the in situ process is simple and it enhances the overall electrochemical performance, which enables the widespread intrusion of ZMPBs and ZMPSs into the application domain. Indeed, considering the promising aspects of the proposed ZIP and its easy processability, this work opens up a new direction for the emergence of the zinc-based energy storage technologies.
Keywords: nonaqueous electrolytes; polymer electrolytes; postlithium batteries; Supercapacitors; zinc-metal batteries

In situ polymerization process: an essential design tool for lithium polymer batteries dagger - Vijayakumar, Vidyanand; Anothumakkool, Bihag; Kurungot, Sreekumar; Winter, Martin; Nair, Jijeesh Ravi (Energy & Environmental Science, 2021)
Polymer electrolytes (PEs), a type of solid-state electrolytes (SSEs), have been in contention for nearly half a century to replace organic liquid electrolytes (LEs) that are used in state-of-the-art lithium-ion batteries (LIBs). They are envisaged to accelerate the industrial-scale production of safe, energy-dense, flexible, and thin lithium polymer batteries (LPBs). LPBs are expected to be widely employed for electric propulsion and other futuristic applications, such as flexible electronics and the Internet of Things (IoT). Even though several polymer architectures and chemistries have been attempted so far, PEs that can outperform LEs remain a real challenge. Apart from inadequate Li+-ion transport properties, challenges concerning the integration of PEs and the engineering of compatible, robust, and durable interfaces and interphases at both the electrodes of LPBs must be appropriately addressed. Recently, the in situ polymerization process has been widely employed as a robust fabrication tool for surpassing the intricacies related to the integration of PEs in LPBs. Hence, in this review, we focus on the in situ polymerization processes that employ various polymerization methods (e.g., free-radical polymerization, ionic polymerization, electropolymerization, condensation polymerization, etc.), functional monomers and oligomers (e.g., acrylate, methacrylate, allyl and vinyl ethers, epoxides, etc.), and PE integration strategies for the fabrication of lithium (ion and metal) polymer batteries (LIPBs and LMPBs). Additionally, this review also evaluates the approaches that have been developed until now to implement the in situ processing of LPBs from large-sized pouch cells to flexible-/printable-batteries and even microbatteries.

2D layered nanomaterials as fillers in polymer composite electrolytes for lithium batteries - Vijayakumar, Vidyanand; Ghosh, Meena; Asokan, Kiran; Sukumaran, Santhosh Babu; Kurungot, Sreekumar; Mindemark, Jonas; Brandell, Daniel; Winter, Martin; Nair, Jijeesh Ravi (Advanced Energy Materials, 2023)
Polymer composite electrolytes (PCEs), i.e., materials combining the disciplines of polymer chemistry, inorganic chemistry, and electrochemistry, have received tremendous attention within academia and industry for lithium-based battery applications. While PCEs often comprise 3D micro- or nanoparticles, this review thoroughly summarizes the prospects of 2D layered inorganic, organic, and hybrid nanomaterials as active (ion conductive) or passive (nonion conductive) fillers in PCEs. The synthetic inorganic nanofillers covered here include graphene oxide, boron nitride, transition metal chalcogenides, phosphorene, and MXenes. Furthermore, the use of naturally occurring 2D layered clay minerals, such as layered double hydroxides and silicates, in PCEs is also thoroughly detailed considering their impact on battery cell performance. Despite the dominance of 2D layered inorganic materials, their organic and hybrid counterparts, such as 2D covalent organic frameworks and 2D metal-organic frameworks are also identified as tuneable nanofillers for use in PCE. Hence, this review gives an overview of the plethora of options available for the selective development of both the 2D layered nanofillers and resulting PCEs, which can revolutionize the field of polymer-based solid-state electrolytes and their implementation in lithium and post-lithium batteries.
Keywords: 2D materials; clay minerals; covalent organic frameworks; metal-organic frameworks; MXene; polymer composite electrolyte; solid-state batteries